Smooth surfaces in very thin GdBa2Cu3O7Î´films for application in superconducting tunnel junctions - Navarro, H.; Sirena, M.; Kim, J.; Haberkorn, N.; Haberkorn, Néstor (Elsevier, 2015)
Fil: Navarro, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; University of California; Estados Unidos